Jet lag - Lee, Christopher J. (Object lessons, 2017)
"Object Lessons is a series of short, beautifully designed books about the hidden lives of ordinary things. What exactly is jet lag? And, more importantly, how do we live with jet lag? Christopher J. Lee's book introduces jet lag as an object of study, tracing medical, temporal, and technological approaches for understanding this strange, hidden cost of our populist cosmopolitanism today. Drawing upon personal experience and an array of cultural registers, Jet Lag considers this present-day Icarian experience to be an allegory of our intrinsic human limits in the face of modern technological change. Jet lag is revealed to be an unavoidable discomfort, an existential condition that is the result of the human body and its inner clock being pitched against the time-leaping effects of modern aviation technologies. Object Lessons is published in partnership with an essay series in The Atlantic."...